Use of Andrographis paniculata (Burm.f.) Wall. ex Nees and risk of pneumonia in hospitalised patients with mild coronavirus disease 2019: A retrospective cohort study - Tanwettiyanont, Jeeranan; Piriyachananusorn, Napacha; Sangsoi, Lilit; Boonsong, Benjawan; Sunpapoa, Chamlong; Tanamatayarat, Patcharawan; Na-Ek, Nat; Kanchanasurakit, Sukrit (Frontiers in Medicine, 2022)
Background Andrographis paniculata (Burm.f.) Wall. ex Nees (AP) has been widely used in Thailand to treat mild COVID-19 infections since early 2020; however, supporting evidence is scarce and ambiguous. Thus, this study aimed to examine whether the use of AP is associated with a decreased risk of pneumonia in hospitalised mild COVID-19 patients. Materials and methods We collected data between March 2020 and August 2021 from COVID-19 patients admitted to one hospital in Thailand. Patients whose infection was confirmed by real-time polymerase chain reaction, had normal chest radiography and did not receive favipiravir at admission were included and categorised as either AP (deriving from a dried and ground aerial part of the plant), given as capsules with a total daily dose of 180 mg andrographolide for 5 days or standard of care. They were followed for pneumonia confirmed by chest radiography. Multiple logistic regression was used for the analysis controlling for age, sex, diabetes, hypertension, statin use, and antihypertensive drug use. Results A total of 605 out of 1,054 patients (mostly unvaccinated) were included in the analysis. Of these, 59 patients (9.8%) developed pneumonia during the median follow-up of 7 days. The incidence rates of pneumonia were 13.93 (95% CI 10.09, 19.23) and 12.47 (95% CI 8.21, 18.94) per 1,000 person-days in the AP and standard of care groups, respectively. Compared to the standard of care group, the odds ratios of having pneumonia in the AP group were 1.24 (95% CI 0.71, 2.16; unadjusted model) and 1.42 (95% CI 0.79, 2.55; fully adjusted model). All sensitivity analyses were consistent with the main results. Conclusion The use of AP was not significantly associated with a decreased risk of pneumonia in mild COVID-19 patients. While waiting for insights from ongoing trials, AP’s use in COVID-19 should be done with caution.